Somalia - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
This report presents the first official debt sustainability analysis undertaken for Somalia. Based on both external and public debt indicators, Somalia is in debt distress. Total public debt is very high, at dollar 4.8 billion, or 101 percent of GDP at end-2018—nearly all of which is external (100 percent of GDP). The finding that Somalia is in debt distress reflects the high external arrears on debt relative to GDP, which now represent 96 percent of the debt stock. While Somalia has no capacity to access new financing, its debt burden will continue to increase as late interest on arrears continues to accumulate. Under broadly steady state assumptions, Somalia’s total public debt is expected to increase to around 128 percent of GDP by 2039. Key risks that affect the outlook include external financing, security, and climate, further highlighting the unsustainability of Somalia’s current debt burden. Consequently, in the absence of debt relief, Somalia will remain in debt distress.